Modelling protein-protein interactions for the design of vaccine chimeric antigens with protective epitopes - Marinela Contreras; Marta Rafael; Isidro Sobrino; Consuelo Almazán; Juan J. Pastor Comín; James J. Valdés; Carlos Roberto Prudencio; Daniel Ferreira de Lima Neto; Veniamin A. Borin; Pratul K. Agarwal; Paul D. Kasaija; Rubén Fernández-Melgar; et al. (PLoS ONE, 2025)
Ticks and tick-borne diseases are a growing burden worldwide and vaccines are effective control interventions. Vaccine formulations with tick antigens such as BM86/BM95 (BM) and Subolesin (SUB) have shown reduction in tick fitness and infestation in immunized hosts. However, antigen combination is a challenging approach to improve vaccine efficacy (E) against multiple tick species. Herein, in silico and in music algorithms were integrated to model BM-SUB protein-protein interactions to apply a quantum vaccinology approach for combining protective epitopes or immunological quantum in the chimeric antigen Q38-95. Cattle immunized with Q38-95 and infested with African blue tick Rhipicephalus decoloratus showed an 82% E similar to BM86 and higher than SUB. The immune mechanisms activated in cattle in response to vaccination with Q38-95 were mediated by anti-BM/SUB antibodies that interfered with BM-SUB interactions and through activation of other innate and adaptive immune pathways. The results support modelling protein-protein interactions affecting E to identify and combine candidate protective epitopes in chimeric antigens.